2020
DOI: 10.1609/icaps.v30i1.6744
|View full text |Cite
|
Sign up to set email alerts
|

– D3WA+ – A Case Study of XAIP in a Model Acquisition Task for Dialogue Planning

Abstract: Recently, the D3WA system was proposed as a paradigm shift in how complex goal-oriented dialogue agents can be specified by taking a declarative view of design. However, it turns out actual users of the system have a hard time evolving their mental model and grasping the imperative consequences of declarative design. In this paper, we adopt ideas from existing works in the field of Explainable AI Planning (XAIP) to provide guidance to the dialogue designer during the model acquisition process. We will highligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Model reconciliation (Chakraborti et al 2019;Sreedharan et al 2019) states that the role of an explanation technique is to bridge the gap between model and user's perception of such model by providing the user with knowledge that might be missing. Model Acquisition (Sreedharan et al 2020) aims to move the actual model (revealed model) towards an ideal model intended by the designer (mental model).…”
Section: Related Work Ai Planning Explanationsmentioning
confidence: 99%
“…Model reconciliation (Chakraborti et al 2019;Sreedharan et al 2019) states that the role of an explanation technique is to bridge the gap between model and user's perception of such model by providing the user with knowledge that might be missing. Model Acquisition (Sreedharan et al 2020) aims to move the actual model (revealed model) towards an ideal model intended by the designer (mental model).…”
Section: Related Work Ai Planning Explanationsmentioning
confidence: 99%
“…In the original work, the space of excuses was confined to initial state changes only, as described above in Definition 4. Since then, the notion of excuses was extended to generic revision of planning tasks [34], and several works have used it as a means to debug planning models in domain authoring tasks such as goal-oriented conversational agents, decision support systems, intelligent tutoring systems [35][36][37].…”
Section: The Guided Demonstration Taskmentioning
confidence: 99%
“…In [27], authors introduced a vocabulary for triaging composed processes iteratively through a mixture of foils, landmarks (i.e. necessary steps), and abstractions.…”
Section: Interpretability and Authoring Toolsmentioning
confidence: 99%